Children’s emerging concepts of resilience: insights from using body mapping in an East London cohort sample of 7-10-year-old children - Murray, Aisling; Smith Scott, Dominie Mahala; Nikolajeva, Milena; Porricelli, Daniele; van Loggerenberg, Francois; Ougrin, Dennis; Lau, Jennifer Y. F. (Frontiers in Psychology, 2025)
BackgroundUnderstanding resilience factors in children is essential for developing early mental health interventions. Middle childhood is an understudied developmental stage, with many quantitative measures lacking validation for this age group and not capturing diverse experiences. This study aimed to use body mapping, an arts-based method, as a novel approach to understand 7-10-year-old children’s concepts of resilience (including definitions and factors that contribute to resilience) in East London. An advisory group of six children commented on the findings.MethodsBody mapping was included in the Development of Emotional Resilience (DEER) Study. Participants drew a resilience symbol, wrote recent worries and colored on an A4-sized body map to signal where they embody stress. Demographic data were collected via self- and parent-report surveys and school records. Manifest content analysis identified four thematic categories related to worries, somatic stress and resilience.Results196 children (48.47% boys, 46.43% girls; 35.20% White, 30.10% Asian, 11.22% Black) across school years 3–5 completed body mapping. Concepts of resilience included perseverance and metaphorical representations of personal strength. We also identified socioecological factors that contributed to resilience, mainly at the individual and interpersonal levels. Boys more often depicted Sports whilst more girls depicted Engagement in the arts and Social networks. 11 worry categories emerged, including education, relationships and physical health. Of the body categories colored (n = 51), the most common were the head, hands and abdomen/stomach.ConclusionChildren expressed dominant and abstract symbols of resilience and identified factors that contributed to resilience. Hobbies and strong relationships may be particularly important in middle childhood, corroborated by the advisory group’s experiences. Body mapping revealed diverse worries (e.g., education, change and uncertainty and global and societal concerns) and somatic experiences of stress (e.g., the head, chest and torso). Through prioritising children’s perspectives, body mapping holds promise in clinical and educational settings.